An exploration of the psychological significance of soap opera viewing - Moodley, Prevan (Rhodes University, Faculty of Humanities, Department of Psychology, 1998)
In traditional research approaches, soap opera viewing has been studied quantitatively. Such studies ignore the subjectivities, the sociocultural contexts, and life contexts of individual viewers. To account for such shortcomings and to offer a qualitative research approach, an investigation was conducted into the engagement that viewers have with a particular soap opera, The bold and the beautiful. The collective case study research method was used. Three subjects were interviewed using in-depth phenomenological interviewing and the data obtained was subjected to.a hermeneutic method of investigation. This involved using a reading guide that extracted firstly, how pleasure is experienced in soap opera viewing, and secondly how the viewers' interpretations of the soap opera are linked to their everyday life contexts. Pleasure was found to be related to experiencing the soap opera world as real, the social context of the viewer, the openness of the text, selecting textual elements, identification and opening up the viewer's world. The viewers' interpretations were related to their life contexts in terms of the meanings that were constructed around emotions, identities, interpersonal relations and a cultural interface. Most notable for the South African context, is that viewing The bold and the beautiful provides a cultural interface because African identities are brought to this practice.
Keywords: Television -- Psychological aspects; Television soap operas -- Psychological aspects